The role of small open reading frames in Shewanella oneidensis phage λSo in host takeover and phage proliferation - Thöneböhn, Svenja Wiebke; Justus Liebig University Giessen (My University, 2025)
Bacteriophages are the most abundant biological entities on Earth. They wield an immense influence on microbial ecosystems in almost all habitats by regulating bacterial population dynamics. Most phages follow one of two well-characterised strategies for host exploitation: the lytic or the lysogenic cycle. In both pathways, host cell lysis represents the terminal event and is therefore central to phage fitness. The temperate phage λSo is one of four known prophages in the genome of Shewanella oneidensis MR-1 and has a genome size of about 51 kbp. During lysogeny, λSo remains integrated into the host chromosome, replicating in concert with the host cell. In this study, the lysis system of λSo was characterised as a pinholin-SAR endolysin-two-component spanin pathway. The λSo holin protein, SSo, contains two transmembrane do-mains and also produces an antagonistic isoform through an alternative translation start, named antiholin. This regulatory mechanism enables precise temporal control over the in-itiation of host lysis. In addition to the pinholin and the SAR endolysin, the lysis system requires a two-component spanin complex, made up of an inner membrane protein (i-Spanin, RzSo) and an outer membrane protein (o-Spanin, Rz1So). The corresponding genes are present in an overlapping reading frame structure, and the encoded proteins likely form a functional dimer of two dimers. This putative dimer enables the fusion of the inner and outer membrane. In addition, this work has shown that further, previously uncharacterised gene products are involved in cell lysis. Like many phages, λSo harbours genes encoding small proteins of unknown function. A gene cluster, so called cluster C, was identified, whose deletion significantly reduced the number of plaque-forming units. Cluster C consists of six genes (lcc1 - lcc6) encoding proteins between 41 and 137 amino acids in length that have no obvious homologies to known protein domains. Bioinformatic analysis suggests that Lcc4 and Lcc6 contain putative transmembrane domains. Functional characterisation revealed that Lcc6 plays a critical role in phage-induced host cell lysis. In lcc6 deletion strains, induction of the lytic cycle of λSo using mitomycin C resulted in the formation of phage particles, which, however, failed to lyse the host cells and are therefore not released. These findings suggest that Lcc6 participates in an early phase of the lysis cascade, likely acting in concert with pinholin-mediated membrane disruption. The ectopic expression of the Lcc4 protein on the other hand resulted in a pronounced elongation of the host cells and delocalisation of the FtsZ rings - a phenotype that is compatible with a disruption of cell division. The modelling of plausible protein interactions confirmed that this phenotype results from a direct interaction of Lcc4 with key components of the bacterial divisome, particularly FtsZ and ZipA. Site-directed mutagenesis identified isoleucine residues at positions 16 and 19 as essential for the interaction with FtsZ, and tryptophan 80 and arginine 84 as critical for binding to ZipA. Taken together, these results suggest that Lcc4 specifically inhibits bacterial cytokinesis following prophage induction in order to maximise the availability of the metabolic resources of the host cell during phage replication. The Lcc proteins, encoded by genes of the cluster C, thus represents a previously undescribed phage-host effector system with profound influence on cellular organisation and the course of lysis.
Keywords: ddc:570